PENGARUH KARATERISTIK PERUSAHAAN, STRUKTUR KEPEMILIKAN, DAN GOOD CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN TRIPLE BOTTOM 'LINE PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI TAHUN 2014-2016 - Yunina, Yunina; Fadillah, Nur (Department of Accounting, Faculty of Economics & Business, 2019)
This study aimed to know the influence of company characteristics, ownership structure and good corporate governance on the disclosure of the Triple Bottom Line. The samples of this research were taken using purposive sampling based on certain criteria and the samples were 23 companies from a population of 45 companies. This study used multiple regression analysis with hypothesis testing using SPSS 17 for Windows. The results showed that leverage, Profitability, and foreign ownership did not have a significant effect on the level of triple bottom line disclosure, institutional ownership, ownership, board size and audit committee size did not significantly affect the triple bottom line disclosure level. While liquidity, industry type and company age significantly influenced the triple bottom line disclosure level. For the next researcher, it is better to use other variables and the number of years extended to be more relevant.